2007
DOI: 10.1186/cc5813
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and serum concentrations of vitamin A in septic patients

Abstract: Sepsis, the body's response to infection, is associated with extremely high mortality rates. Why a protective mechanism turns into a deadly clinical picture is a matter of debate, and goes largely unexplained. In previous work we demonstrated that platelet-derived microparticles (MP) can induce endothelial and vascular smooth muscle cell apoptosis in septic patients through NADPH oxidasedependent superoxide release [1]. In this work we sought to create a model for ex vivo generation of septic-like MP and to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Our study identified vitamins A and D as potent immunomodulators, that might be of particular importance in systemic infections, where the dysregulation of the immune response is responsible for the fatal outcome555964. Moreover, recent studies have described important inadequacies of retinol65 and vitamin D66 in critically ill patients, and associated this deficiency with increased risk of mortality. Thus, monitoring the serum levels of vitamins A and D, as well as its adequate supplementation in individuals admitted in intensive care units, might have far-reaching prophylactic and therapeutic implications in severe infections.…”
Section: Discussionmentioning
confidence: 75%
“…Our study identified vitamins A and D as potent immunomodulators, that might be of particular importance in systemic infections, where the dysregulation of the immune response is responsible for the fatal outcome555964. Moreover, recent studies have described important inadequacies of retinol65 and vitamin D66 in critically ill patients, and associated this deficiency with increased risk of mortality. Thus, monitoring the serum levels of vitamins A and D, as well as its adequate supplementation in individuals admitted in intensive care units, might have far-reaching prophylactic and therapeutic implications in severe infections.…”
Section: Discussionmentioning
confidence: 75%
“…Oxidative stress also plays important roles in its pathophysiology. Previous studies reported increased oxidant marker levels, and decreased antioxidant marker levels in sepsis (13)(14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 92%